Disperse Dyes: Synthesis of 2,4’-Dichloro Diphenyl Ether 4-(Aryl Azo) Dyes and Their Application to Polyester fabric - Desai, K.R.; Desai, C.K. (Asian Journal of Chemistry, 2010)
Attempts have been made to prepare disperse dyes based on aryl ether. 4-Amino-2,4'-dichloro diphenyl ether was diazotized and coupled with various diazo components. These compounds were evaluated for the dyeing properties on polyester fibre. The structures of these compounds have been confirmed by elemental analysis and IR spectral studies.